Culturas pedagógicas de docentes indígenas Cabécares. Una mirada a su trabajo áulico - Gutiérrez Hernández, Mónica (Universidad de Costa Rica, 2024)
This article presents a research initiative that made an approach, in a respectful manner,to the school history of five Cabécar indigenous people from the territory of Chirripó-Duchíi (as it is called among the Cabécar people), who are in the teaching exercise of the Cabécar Language and Culture Program of the Ministry of Public Education. The general objective was to analyze narratives of the school stage and classroom work of Cabecar indigenous teachers of Chirripó in order to identify didactic elements that contribute to teaching with cultural relevance, which was achieved through the socialization of narratives and observations that allowed identifying didactic elements that could add to the efforts to offer the children of these communities an education in accordance with their worldview and their environment. This is a study that, due to its characteristics, was registered as an exploratory and descriptive type of research. Among the main results, the study made it possible to recognize that, despite the fact that the school education to which the teachers were subjected was mediated by the dominant culture, they made important efforts to deconstruct the asymmetrical relations with a bias towards western culture, giving place to the extent of their possibilities to the native culture, and the recognition of cultural diversity.